Analysis of fractional anisotropy and mean diffusivity in refractory and non-refractory idiopathic generalized epilepsies. (November 2018) - Lobato, Mauricio; Garcia, Lucas; Amaro, Edson; Otaduy, Maria; Jorge, Carmen; Castro, Luiz H
Highlights: Idiopathic generalized epilepsies (IGEs) usually present normal MRI findings. Thalamic, corpus callosum and frontal abnormalities have been reported in IGEs. We evaluated white matter changes in refractory and non-refractory IGE patients. We found diffuse white matter involvement (FA and MD) in our IGE patient population. We found no differences in DTI indices between refractory and non-refractory IGE. Abstract: Purpose: To compare white matter bundles and fiber tract changes in seizure-free and non-seizure-free idiopathic generalized epilepsy (IGE) patients. Method: Forty adult patients with IGE underwent a 3 T brain MRI with DTI sequences. According to seizure control status, eighteen patients were classified as refractory (R) if they had presented at least one incapacitating seizure in the previous six months, while on appropriate antiepileptic drug treatment. Twenty two seizure-free patients with adequate seizure control were considered non-refractory (NR). We compared fractional anisotropy (FA) and mean diffusivity (MD) values in sixteen white matter tracts in the R and NR groups, and in twenty healthy subjects. Results: R and NR groups did not differ in gender, age and education. We found decreased FA in two tracts in the R group (forceps major and right uncinate fasciculus) and approaching statistical significance in two tracts in the NR group (right cingulate gyrus and right uncinate fasciculus) group, as well as increased MD in six tracts in the R group (forceps minor, left thalamic anterior radiation, right inferior longitudinal fasciculus, right longitudinal superior parietal and temporal fasciculi, and right cingulate gyrus) and in five tracts in the NR group (forceps minor, left thalamic anterior radiation, right inferior longitudinal fasciculus, right longitudinal superior parietal and temporal fasciculi), compared to controls. No differences were noted comparing FA and MD values between R and NR groups. Conclusions: In our patient population, refractory IGE patients on adequate antiepileptic drug treatment did not present more severe white matter tract involvement compared to non-refractory patients.